1970
DOI: 10.1099/00221287-63-3-303
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Dipicolinic Acid to Heat Resistance of Bacterial Spores

Abstract: S U M M A R YSpores of five strains of Clostridium botulinum differing widely in their heat resistance contained 7.4 to 13-4 % dipicolinic acid. There appeared to be no correlation between DPA content and heat resistance of the various strains. The rate of loss of DPA during heating at 75 and IOOO was consistently slower than the rate of loss of spore viability, though, in general, heat-resistant strains lost DPA less quickly than did heat-sensitive strains.At the instant of thermal death, spores still retaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1973
1973
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Murrell (1969) concluded that the spore DPA content was not the determining factor in the degree of heat resistance. Our proposal (Brown & Melling, 1967) that the nature of the DPA bonds rather than the amount of DPA was the determining factor for dormancy and resistance has received further support by Grecz & Tang (1970) and Grecz, Tang & Rajan (1972). These workers studied the stability of Ca2+-DPA complexes in relation to pH and temperature.…”
Section: Discussionmentioning
confidence: 89%
“…Murrell (1969) concluded that the spore DPA content was not the determining factor in the degree of heat resistance. Our proposal (Brown & Melling, 1967) that the nature of the DPA bonds rather than the amount of DPA was the determining factor for dormancy and resistance has received further support by Grecz & Tang (1970) and Grecz, Tang & Rajan (1972). These workers studied the stability of Ca2+-DPA complexes in relation to pH and temperature.…”
Section: Discussionmentioning
confidence: 89%
“…Recent threats of contamination in the United States and the continuing danger to military personnel and civilians alike indicate the need for a detector of biological agents that operates in real time and that can function in a variety of environments. Several methods for detection of bacterial spores have been developed including PCR [2,3], immunofiltration assay [4,5], polymorphism analysis [6], direct detection of DNA sequences [7], liquid chromatography [8], FT-IR [9] and those which indicate bacterial spore presence by detection of DPA [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The release of Dpa from spores during heat treatment and its relation to heat resistance has been studied in B. megaterium (Rode & Foster 1960) in 8. subtilis and B. megaterium (El-Bisi et urn (Grecz & Tang 1970) and in B. megaterium (Hodges & Brown 1975). The same conclusion was reached in all these studies: that release of Dpa proceeds at a slower rate than loss of viability of spores during heating, suggesting that death precedes the release of Dpa.…”
mentioning
confidence: 99%